1984
DOI: 10.1007/bf00286601
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the gene for uroporphyrinogen decarboxylase to human chromosome 1 by somatic cell hybridization and specific enzyme immunoassay

Abstract: A specific enzyme immunoassay of uroporphyrinogen decarboxylase was developed and applied to the detection of the human enzyme in man-rodent somatic cell hybrids. This method allowed to assign the gene for uroporphyrinogen decarboxylase to human chromosome 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The excess zinc protoporphyrin in erythrocytes is probably formed from pathway intermediates that accumulate during hemoglobin synthesis and are later metabolized to protoporphyrin, and then complexed with zinc (Phillips et al, ). HEP is the recessive form of type 2 PCT, an autosomal dominant condition in which heterozygous UROD mutations predispose carriers to clinical manifestations (Verneuil et al, ,b).…”
Section: Non‐acute Hepatic Porphyriasmentioning
confidence: 99%
See 1 more Smart Citation
“…The excess zinc protoporphyrin in erythrocytes is probably formed from pathway intermediates that accumulate during hemoglobin synthesis and are later metabolized to protoporphyrin, and then complexed with zinc (Phillips et al, ). HEP is the recessive form of type 2 PCT, an autosomal dominant condition in which heterozygous UROD mutations predispose carriers to clinical manifestations (Verneuil et al, ,b).…”
Section: Non‐acute Hepatic Porphyriasmentioning
confidence: 99%
“…Patients are either homozygous or compound heterozygous for UROD mutations, and at least one allele must express some UROD enzymatic activity, since a null mutation would be lethal in the homozygous state (Elder et al, ; Verneuil et al, ,b). Thus, null mutations are much less common in HEP than in heterozygotes with type 2 PCT (Phillips et al, ).…”
Section: Non‐acute Hepatic Porphyriasmentioning
confidence: 99%
“…The genetic locus encoding for URO-D is mapped on human chromosome 1 (Verneuil et al 1984b) and the cloning and sequencing of the gene (Romana et al 1987) allowed to find out genetic defects associated to familial PCT (f-PCT) and to HEP. So far, 39 different mutations in the UROD gene have been identified and the molecular analysis has confirmed that HEP is the homozygous form of f-PCT (Garey et al 1989, Garey et al 1990, Romana et al 1991, Verneuil et al 1992, Roberts et al 1995, Moran-Jimenez et al 1996, Mendez et al 1998, McManus et al 1999, Christiansen et al 1999, Mendez et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases with hereditary autosomic dom inant transmission, a decrease of about 50% of the activity o f the erythrocytic uro decarboxylase is observed in erythrocytes, hepatocytes, lymphocytes and fibroblasts [3], Morphologically, the characteristics of SPCT and FPCT are almost identical and can be controlled with the same therapy.…”
Section: Discussionmentioning
confidence: 76%